Influence of Modulated Photo-Activation on Shrinkage Stress and Degree of Conversion of Bulk-Fill Composites - Velo,Marilia Mattar de Amoêdo Campos (2019)
Abstract This study aimed to evaluate the polymerization properties of bulk-fill materials (low and high-viscosity) by using high-intensity continuous light and intermittent photo-activation in terms of polymerization shrinkage stress and degree of conversion (DC). The following Bulk-fill and Conventional nanofilled resin composites were evaluated: Filtek Z350XT Flow (3M/ESPE), SureFil SDR Flow (Dentsply), Filtek Bulk Fill Flow (3M/ESPE), Filtek Z350XT (3M/ESPE) and Filtek Bulk Fill Posterior (3M/ESPE). A LED device (DB 685, Dabi Atlante) was used for both protocols: continuous uniform and intermittent photo-activation (light-on and light-off cycles) with identical radiant exposure (14 J/cm2). The polymerization shrinkage stress (n=6) was evaluated by inserting a single increment of 12 mm3 between two stainless steel plates (6×2 mm) adapted to a Universal Testing Machine (UTM), at different times. Measurements were recorded after photo-activation. The degree of conversion was evaluated by Fourier transformed infrared spectroscope (FTIR) with an attenuated total reflectance (ATR) accessory (n=5). Data were analyzed by three-way ANOVA and Tukey’s HSD (α=0.05) tests. Bulk Fill Posterior presented higher shrinkage stress values when photo-activated with the intermittent technique (p<0.05). The intermittent photo-activation increased the degree of conversion for the low-viscosity bulk-fills (p<0.05). Therefore, the use of modulated photo-activation (intermittent) must be indicated with caution since its use can influence the shrinkage stress and degree of conversion of composites, which varies according to the resin formulations.